The Embodied Moral Mind: an Approach to the Embodied Nature of Moral Cognition - Olivera La Rosa, Antonio (Pensando Psicología, 2013)
Diverse studies carried out over the last decade suggest that moral cognition is widely supported by automatic psychological processes. In this context, the existing psychological correspondence between certain corporal states and cognitive processes (embodiment) has been widely documented in studies associated with morality. Therefore, the present review aims to clarify the nature of the corporal component of our moral cognition, with particular emphasis on the interdependent relationship between the emotion of repugnance, the sensation of physical cleanliness and moral judgments. The conclusion is that, while the automatic nature of moral cognition seems to facilitate the occurrence of embodiment, the evidence suggests that the nature of corporal metaphors in our moral life is variable.
Keywords: automatic nature; moral cognition; embodiment; moral judgments; repugnance